2020
DOI: 10.1101/2020.04.03.024281
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Expansion of the circadian transcriptome inBrassica rapaand genome-wide diversification of paralog expression patterns

Abstract: An important challenge of crop improvement strategies is assigning function to paralogs in polyploid crops. Gene expression is one method for determining the activity of paralogs; however, the majority of transcript abundance data represents a static point that does not consider the spatial and temporal dynamics of the transcriptome. Studies in Arabidopsis have estimated up to 90% of the transcriptome to be under diel or circadian control depending on the condition. As a result, time of day effects on the tran… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 57 publications
0
4
0
Order By: Relevance
“…Our understanding of plant chronobiology and diel plant cell regulation has been significantly enhanced through gene expression studies, driven by the evolution of technologies from single‐gene quantitative PCR (qPCR) to systems‐level tools such as microarrays and RNA sequencing (RNA‐seq) (Maric and Mas, 2020). Time‐course transcriptomics experimentation has provided, and continues to provide, us with a wealth of knowledge of diel gene regulation across a range of organisms, including Arabidopsis (Kamioka et al ., 2016), soybean ( Glycine max ) (Li et al ., 2019), lettuce ( Lactuca sativa ) (Higashi et al ., 2016) and Brassica rapa (Greenham et al ., 2020). Recently, extensive transcriptomic characterisation of a suite of circadian clock mutants in Arabidopsis has revealed that individual clock components appear to regulate distinct portfolios of genes (Graf et al ., 2017).…”
Section: Introduction: the Transcriptome‐centred Understanding Of Plant Chronobiologymentioning
confidence: 99%
“…Our understanding of plant chronobiology and diel plant cell regulation has been significantly enhanced through gene expression studies, driven by the evolution of technologies from single‐gene quantitative PCR (qPCR) to systems‐level tools such as microarrays and RNA sequencing (RNA‐seq) (Maric and Mas, 2020). Time‐course transcriptomics experimentation has provided, and continues to provide, us with a wealth of knowledge of diel gene regulation across a range of organisms, including Arabidopsis (Kamioka et al ., 2016), soybean ( Glycine max ) (Li et al ., 2019), lettuce ( Lactuca sativa ) (Higashi et al ., 2016) and Brassica rapa (Greenham et al ., 2020). Recently, extensive transcriptomic characterisation of a suite of circadian clock mutants in Arabidopsis has revealed that individual clock components appear to regulate distinct portfolios of genes (Graf et al ., 2017).…”
Section: Introduction: the Transcriptome‐centred Understanding Of Plant Chronobiologymentioning
confidence: 99%
“…The pan-genomes of Brassica napus, B. rapa, and B. oleracea (references within Bayer et al, 2020), have genes with PAV that associate with stress response. In B. rapa, the expansion of the circadian transcriptome resulted in divergence in phasing among retained paralogs, as well as differential drought responses (Greenham et al, 2020). A QTL study in B. rapa uncovered GI contributing to natural variation in circadian period, and salt and cold tolerance (Xie et al, 2015), which aligns with a conserved role for GI in abiotic stress response in Arabidopsis (Seo & Mas, 2015).…”
Section: Brassicasmentioning
confidence: 91%
“…Widespread whole genome duplications gave rise to an expanded circadian clock system in angiosperms (Lou et al ., 2012; Greenham et al ., 2020). The RVE/LHY/CCA1 family, with three copies in the basal angiosperm Amborella trichopoda ( LHY , RVE1 and RVE6 ), has expanded to seven copies in rice (Fig.…”
Section: The Origins Of Clock‐mediated Abiotic Stress Response In the Green Lineagementioning
confidence: 99%
See 1 more Smart Citation